Cooperation for a peaceful and sustainable world - Junsheng, Li.; Bo, Chen.; Na, Hou. (Bingley, U.K. : Emerald, 2013)
Part 2 of the Cooperation for a peaceful and sustainable world volume, brings together some of the leading researchers on peace science. Chapters discuss issues including, but not restricted to, military expenditure and economics in China, India and Pakistan, Peace science in South East Asia, and approaches to anti-terrorism.
Is China the second military power? A defense industry prospective / Huang Chaofeng -- Defense expenditure, budget deficits, and income distribution in India (1970-2009) / Zhonghou Guo, Yiwen Jiang, Huibin Yu -- Defense expenditure and economic growth under external predation / Liu Taoxiong, Hu Angang -- Terrorism and intelligence-led counterterrorism in China / Wang Shacheng -- China-Africa relations : making sense of the discourse / Seifudein Adem -- Rational model of conflict : war and peace in South Asia / Richard Barrett, Samir Deger-Sen, Somnath Sen -- Military Keynesianism : an assessment / J. Paul Dunne -- Debt and peace in post-conflict countries / Fabrizio Carmignani -- Indian commitment to no first use of nuclear weapons : first step toward global nuclear disarmament / P.M. Kamath -- Sri Lanka : ethnic conflict and the conflict management process / Prashant Amrutkar -- Four studies in non-state experiments with peacemaking in contemporary India / Samir Kumar Das -- Military expenditure and economic growth in South Asia / Hou Na, Chen Bo -- Is China an emerging sanctioning state? / Liu Jianwei.
Includes index.
Print version record
Keywords: Political Science -- General; Political science & theory; Peace -- Economic aspects; Peace-building -- Economic aspects; Econometric models